HUBUNGAN ANTARA KARAKTERISTIK ORANG TUA DENGAN STRES PENGASUHAN PADA ORANG TUA ANAK GANGGUAN SPEKTRUM AUTISME - Faizah Attamimi Nuha; Asri Mutiara Putri; Nia Triswanti (JURNAL PSIKOLOGI MALAHAYATI, 2020)
ABSTRACT: RELATIONSHIP BETWEEN PARENTAL CHARACTERISTICS AND PARENTING STRESS IN PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDER Autism is a complex developmental disorder, includes disorders of communication, behavior, social skills, sensory and learning caused by brain damage. The level of parenting stress experienced by parents of autistic children is very high. Parental characteristics are one of the factors that influence parenting stress. This study aims to determine the relationship between parental characteristics and parenting stress of parents who have children with autism spectrum disorders. This research is an analytic survey research with a cross-sectional design. The research sample consisted of 31 parents who had children with autism spectrum disorders in special schools in Bandar Lampung. The measuring instruments used are parental demographic data and Parenting Stress Index (PSI). The results showed that most of the respondents were middle adults (61.3%), tertiary education (64.5%), working status (54.8%), had an income more than Rp. 3,500,000 (74.2%) and had moderat level of parenting stress (74.2%). The results of the correlation analysis showed that there was a significant relationship between parental characteristics and parenting stress. Age and education are the strongest factors that predict parenting stress. Keyword: Parenting Stress, Parental Characteristics, Autism Autisme merupakan gangguan perkembangan yang kompleks seperti gangguan komunikasi, perilaku, kemampuan sosialisasi, sensoris dan belajar yang disebabkan oleh kerusakan otak. Tingkat stres pengasuhan yang dialami orang tua anak autis sangat tinggi. Karakteristik orang tua merupakan salah satu faktor yang mempengaruhi stres pengasuhan. Penelitian ini bertujuan untuk mengetahui hubungan karakteristik orang tua dengan stres pengasuhan orang tua yang memiliki anak gangguan spektrum autisme. Penelitian ini merupakan penelitian survei analitik dengan desain cross-sectional. Sampel penelitian berjumlah 31 orang tua yang memiliki anak ganggan spektrum autisme di SLB se-Bandar Lampung. Alat ukur yang digunakan adalah data demografi orang tua dan Parenting Stres Index (PSI). Hasil penelitian menunjukkan sebagian besar responden berusia dewasa madya (61,3%), berpendidikan perguruan tinggi (64,5%), status bekerja (54,8%), memilikipendapatan > Rp.3.500.000 (74,2%) dan memiliki tingkat stres pengasuhan sedang (74,2%). Hasil analisis korelasi didapatkan adanya hubungan yang signifikan antara karakteristik orang tua dengan stres pengasuhan. Usia dan pendidikan menjadi faktor yang paling kuat memprediksi stress pengasuhan. Kata Kunci: Stres Pengasuhan, Karakteristik Orang Tua, Autisme